ANALISIS PENGUJIAN SISTEM INFORMASI RUMAH SAKIT (STUDI KASUS RUMAH SAKIT KHUSUS BEDAH AN NUR YOGYAKARTA) - , ULINNUHA YUDIANSA PUTRA, Gunawan Wibisono, SE., M.Acc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Use of Information Technology Systems in support of operational activities of a company is a very important part. Information technology systems can be used to facilitate data processing companies, speeding up transaction processing can be used as a managerial decision making. However, not all companies that have used information technology systems are successful in developing its business. An information technology system can be said to succeed or suitable to be used by the firms if they meet certain factors. The factors must be in accordance with the characteristics of the information system itself and its users. DeLone and McLean (2003) has provided an overview of the factors that can be used to assess whether an appropriate information system has been used in a company. Factors used in this study is the Quality Systems, Information Quality, Service Quality, User Satisfaction and Net Benefits. The research was conducted at the Hospital for Special Surgery AN NUR Yogyakarta. The object that is used is SIMRS (Hospital Management Information System) with respondents who used the 50 employees who use SIMRS Hospital in support of the work. The purpose of this study was to assess the factors contained in the model of DeLone and McLean (2003). Analysis tools used in this study is Partial Least Square (PLS) The results showed that the factors contained in the model of DeLone and McLean's first, the quality system is not a positive influence on user satisfaction by 0.305 percent. Second, the quality of information has a positive effect on user satisfaction by 5.851 percent. Third, service quality has a positive effect on user satisfaction by 6.670 percent and the fourth, user satisfaction has a positive effect on net benefits amounting to 15.786 percent. So cumulatively, the variety of user satisfaction factor of 71.1 percent can be explained by the quality system, quality information and quality services, while 28.9 percent is explained by other variables. Variance of net benefits can be explained by 37 percent by user satisfaction and 63 percent is explained by other variables.